THE JOKOWI ERA: DID HE DELIVER WHAT HE PROMISE? : (Comparing Three Major Industries’ Performances) - Lenny Gunawan; Adi Kurniawan Yusup (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
Comparative quantitative approach utilized to evaluate Indonesia's financial performance in manufacturing, mining, and infrastructure sectors from 2014 to 2022 from PCT POV. Utilizing secondary data from audited financial statements, the study finds that the manufacturing sector indicated stagnant performance. The final research sample consists of 103 manufacturing, 31 mining, and 23 infrastructure companies. Three analysis stages involved: Descriptive statistics, calculating the mean values each financial sector. Paired-sample t-tests (within-firm comparisons) evaluating a one-tailed hypothesis that performance in 2022 is higher than in 2014. Lastly, the test results interpretation follows standard significance testing procedures (1%, 5%, and 10% significance level) using STATA, In contrast, the mining sector showed significant improvement in asset utilization, liquidity, and profitability, confirming the hypothesis of progress. On the contrary, the infrastructure sector displayed declines in asset turnover and profitability, leading to the rejection of the hypothesis regarding its progress. Factors like foreign investment and operational challenges in the manufacturing and infrastructure sectors are discussed.